2021
DOI: 10.1016/j.annonc.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

EANO–ESMO Clinical Practice Guidelines for diagnosis, treatment and follow-up of patients with brain metastasis from solid tumours

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
310
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(325 citation statements)
references
References 95 publications
6
310
1
8
Order By: Relevance
“…Nowadays, SRS plays an increasingly important role in radiotherapy of patients with BMs. According to the latest guideline [ 10 ], for patients with oligo-BMs, SRS was recommended as preferred radiotherapy mode. Moreover, SRS could also be considered for patients with 4–10 BMs and cumulative tumor volume less than 15 ml or after complete or incomplete resection of BMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, SRS plays an increasingly important role in radiotherapy of patients with BMs. According to the latest guideline [ 10 ], for patients with oligo-BMs, SRS was recommended as preferred radiotherapy mode. Moreover, SRS could also be considered for patients with 4–10 BMs and cumulative tumor volume less than 15 ml or after complete or incomplete resection of BMs.…”
Section: Discussionmentioning
confidence: 99%
“…Not only for patients with oligo-BMs, but also for patients with 4–10 BMs with a cumulative tumor volume of fewer than 15 ml, SRS could also be recommended. WBRT, as an alternative scheme, could be selected for patients with multiple BMs not eligible for SRS, in line with performance status, number, and location of BMs, and neural symptoms [ 10 ]. Nevertheless, WBRT is the primary radiotherapy method for patients with leptomeningeal metastases (LM), though whether it could extend survival remains debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the new European Association of Neuro-Oncology (EANO)–European Society for Medical Oncology (ESMO) clinical practice guidelines, a systemic therapy can play an important role in the control of brain metastases from breast cancer and it should be considered for most patients with initial brain metastases, not only after an intracranial recurrence. In asymptomatic brain metastases, a systemic treatment should be considered to delay WBRT [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial treatment of symptomatic brain metastases (BM) is traditionally local with neurosurgery and/or radiotherapy, depending on the number of metastases, performance status, and systemic disease control. 16 These techniques provide good local control but do not effectively prevent future CNS events. An exploratory analysis of the CLEOPATRA trial showed longer median time to development of CNS metastases as first site of disease progression in pertuzumab arm (15.0 versus 11.9 months, HR 0.58, 95% CI 0.39-0.85), 17 meaning that despite the low blood–brain barrier (BBB) permeability, these monoclonal antibodies still play a role in first-line MBC with BM.…”
Section: Relapse With Central Nervous System Metastasesmentioning
confidence: 99%